AROMA, PENAMPILAN DAN SISA MAKANAN PADA PASIEN KANKER - Kusuma, Hapsari Sulistya; Putri, Astrid Rossalia; Handarsari, Erma (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
AbstractNutrition intake is one ofÂ a key factor that support the medication process of cancer patient. Food waste is mainly found on cancer patients due to several internal and external factors. This research aiming to describe the the flavor, food appearance, and food waste of cancer patients. This research used cross-sectional method that was done to 10 hospitalized cancer patients in Public Hospital (RSUD) of Tugurejo Semarang. The respondents used consecutive sampling during 2 months of research. The research showed scoring of flavor about 46,7% say â€œgoodâ€ and 53,3% say â€œnot goodâ€, and the scoring of food appearance about 67,5% say â€œattractiveâ€ and 32,5% say â€œnot attractiveâ€. The results of food waste showed about, 33.9% for main food, 25.7% for animal based side dishes, 37.5% for non-animal based side dishes and 38.1% for vegetables and 1.1% for fruits. Respondents that declare unsatisfactory aroma have a low appeal to consume the food served because the aroma is able to cause nausea and decreased appetite. The appearance of food served by the hospital is less varied. Both of these reason may increase the food waste.Â Keywords : flavor, food appearance, and food wasteÂ AbstrakAsupan gizi adalah salah satu faktor kunci yang mendukung proses pengobatan pasien kanker. Sisa makanan terutama ditemukan pada pasien kanker karena beberapa faktor internal dan eksternal. Penelitian ini bertujuan untuk mendeskripsikan aroma, penampilan makanan, dan sisa makanan penderita kanker. Penelitian ini menggunakan metode cross-sectional yang dilakukan pada 10 pasien kanker yang dirawat di Rumah Sakit Umum (RSUD) Tugurejo Semarang. Responden menggunakan sampling berurutan selama 2 bulan penelitian. Penelitian menunjukkan skor rasa sekitar 46,7% menyatakan